Synergistic inhibition of HIV-1 infection by combinations of soluble polyanions with other potential microbicides. - Gantlett, K; Weber, J; Sattentau, Q (2007)
Several polyanionic compounds with potential for use as topically applied microbicides to prevent HIV-1 sexual transmission, such as PRO 2000, are currently in phase III clinical efficacy trials. Microbicidal formulations may well comprise combinations of inhibitors to increase potency, reduce dose and minimize problems of HIV-1 resistance. We have therefore evaluated in vitro, the anti-HIV-1 activity of two leading polyanionic microbicides combined with other antiretroviral agents with microbicidal potential. Dextran sulfate (DS) and PRO 2000 were combined with the neutralizing antibody IgG1b12, the peptide-based fusion inhibitor T20, the CCR5 antagonist TAK779 and the cyanobacterial protein cyanovirin-N. Anti-HIV-1 activity was assessed in a single cycle replication assay using pseudoviruses carrying a luciferase reporter gene and the envelope glycoproteins from HIV-1 isolates JR-FL (R5) and HxB2 (X4), against both immortalized and primary CD4+ cell targets. The data were analyzed for synergy using Calcusyn software. Results indicate that PRO 2000 and DS can act synergistically with most inhibitors tested, although the degree of synergy depends on inhibitor concentration and combination. These data provide a rational basis for testing of microbicide combinations in vivo.